Step-by-step explanationStep 1
![\begin{gathered} f(x)=2^x-3 \\ j(x)=x+2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1g6wldc6jjqkxh3f49glz3cyq6mtjjs0my.png)
a) to graph f(x) , we start from the function
![\begin{gathered} f(x)=2^x \\ then,\text{ we shift the graph 3 units down, so} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eqqqmlmom7td2joumcc9yyek18yhi0n6q0.png)
b) j (x) is a line, so we need 2 points
![\begin{gathered} j(0)=0+2=2 \\ P1(0,2) \\ and \\ j(1)=1+2=3 \\ P2(1,3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/wiy4bvzbwn01t0b1nu2y8eoax1ilqxre96.png)
then, draw a line that passes through P1 and P2
finally, the solution is the point where the graph intersect each other, so
so, we can conclude that
the answer is